Improved insecticidal control of spotted wing drosophila (Drosophila suzukii) using yeast and fermented strawberry juice baits. (November 2019) - Noble, Ralph; Dobrovin-Pennington, Andreja; Phillips, Amy; Cannon, Madeleine F.L.; Shaw, Bethan; Fountain, Michelle T.
Abstract: The phagostimulant effect of baits on the Drosophila suzukii control efficacy of different insecticides applied at sub-lethal concentrations was tested in bioassays. The baits were fermented strawberry juice (FSJ), a suspension of the yeast Hanseniaspora uvarum, a combination of the two and Combi-protec, a proprietary mixture of plant extract, proteins and sugars. Without insecticides, the baits did not affect D. suzukii mortality. With spinosad, cyantraniliprole or lambda-cyhalothrin, the baits caused higher mortality of D. suzukii summer morphs, under summer conditions, compared with using the insecticides in water. The mortality and reduced reproduction efficacy of insecticides was greater with H. uvarum, FSJ +  H. uvarum or Combi-protec treatments compared with FSJ only bait. H. uvarum and FSJ baits also increased the mortality of D. suzukii winter morphs, held under winter conditions, when used with spinosad or cyantraniliprole but not with lambda-cyhalothrin. Cyantraniliprole +  H. uvarum also reduced oviposition in winter morphs that were transferred to summer conditions after three days of exposure to treatments under winter conditions. Leaf type did not have an impact on combined bait and insecticide treatments; all were effective when applied to blackberry, blueberry, cherry, raspberry or strawberry leaves. Phagostimulant baits improved the insecticidal control of D. suzukii summer and winter morphs by increasing mortality and reducing oviposition and the lethal dose of insecticides. The relative phagostimulant effect of the baits did not fully correspond with their olfactory attraction to D. suzukii. Highlights: Phagostimulant baits improved the insecticidal control of Drosophila suzukii . Hanseniaspora uvarum, Combi-protec and fermented strawberry juice were effective. Improved control was through increased D. suzukii mortality and reduced oviposition. Insecticidal control of both summer and winter morph D. suzukii was improved by baits.